A subhierarchical parallel computational algorithm for solving problems of diffraction by plane screens - Medvedik, M. Yu; Smirnov, Yu. G. (Journal of communications technology & electronics, 2008)
A subhierarchical method is proposed for solving problems of diffraction by thin plane perfectly conducting screens of an arbitrary shape. The Rao-Wilton-Glisson method is used for numerical solution of the problem. A parallel algorithm is applied to calculate matrix elements and right-hand sides. Screen currents are calculated on a computational cluster.